Remediation of Arsenic-contaminated soils by Iron amendments: a review - Miretzky, Patricia (2010)
Arsenic (As) in soil is a serious environmental issue, and although As occurs naturally in soil, anthropogenic activities have greatly increased As soil contamination. Several technologies can be used to reduce arsenic contamination in soils, among them in situ chemical immobilization by application of inorganic amendments, which are incorporated and mixed with the contaminated soil. The binding of As to the additive reduces its mobility and bioavailability in the soil, with the long-term stability of the new compounds formed being an important issue. The objective of this study was to review the literature concerning remediation of As-contaminated soils with different iron sources and to evaluate their effectiveness.